PALANGAJA Media for Javanese Script Reading Skills - Wahyu Andani; Sukardi (Jurnal Edutech Undiksha, 2023)
Teachers' minimal use of learning media is one factor causing students' lack of interest in Javanese, especially Javanese script material. It affects skills in reading Javanese scripts. This research aims to create PALANGAJA media for Javanese script reading skills. The type of research used is Research and Development (R&D). The development model used is the Borg and Gall model. The research subjects used were 29 fourth-grade elementary school students—the techniques used in collecting data included interviews, questionnaires, tests, and documentation. The initial data analysis technique uses a normality test, and the final data analysis uses the T and N-gain tests. The research results show that the PALANGAJA media has been successfully developed, is suitable for use, and is effective in improving Javanese script reading skills based on learning results assessed by media experts and material experts, with percentages of 78% and 79%, respectively student learning results in the pretest and post-test scores with the t-test obtained count (7.675) more than table (2.051), so Ha was accepted. The n-gain results show a result of 0.563 with medium criteria. The research conclusions show that PALANGAJA media has been successfully developed, is suitable for use, and effectively improves fourth-grade elementary school students' Javanese script reading skills. This research implies that teachers can use PALANGAJA learning media to create a pleasant learning atmosphere for students.